2007
DOI: 10.1007/s00441-007-0468-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of melatonin receptors on pCREB and clock-gene protein levels in the murine retina

Abstract: In several mammalian species, the retina is capable of synthesizing melatonin and contains an autonomous circadian clock that relies on interlocking transcriptional/translational feedback loops involving several clock genes, such as Per1 and Cry2. Our previous investigations have shown remarkable differences in retinae of melatonin-deficient (C57BL) and melatonin-proficient (C3H) mice with regard to the protein levels of PER1, CRY2, and phosphorylated (p) cyclic AMP response element binding protein (CREB). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
(41 reference statements)
2
21
0
Order By: Relevance
“…As previously mentioned, a similar role for melatonin signaling has been also proposed for the retina since it has been reported that melatonin may influence circadian clock gene expression in the retina since the amplitude and the phase of Per1, and Cry1 m RNA and protein in the mouse retina is different between melatonin-proficient, melatonin-deficient mice, and mice lacking melatonin signaling [18][19].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…As previously mentioned, a similar role for melatonin signaling has been also proposed for the retina since it has been reported that melatonin may influence circadian clock gene expression in the retina since the amplitude and the phase of Per1, and Cry1 m RNA and protein in the mouse retina is different between melatonin-proficient, melatonin-deficient mice, and mice lacking melatonin signaling [18][19].…”
Section: Discussionmentioning
confidence: 63%
“…Additional investigations have also indicated that melatonin signaling may modulate clock gene expression in the retina [18]. However, it is important to note that this later study compared clock gene expression between a melatonin-proficient (C3H-HeN) and a melatonin-deficient (C57/Bl6) mouse strain [18] and therefore the observed difference in the expression pattern of expression of the clock genes and/or proteins may be also due to other unknown factors.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Numerous reports demonstrate that melatonin via binding and activation of the MT 1 and MT 2 G protein-coupled receptors, modulates the activity of a variety of G proteins, including Gα i2 , Gα i3 , Gα q , and Gα 11 (Kiefer et al 2002; Lai et al 2008). The MT 1 receptor is coupled to the inhibition of cyclic adenosine monophosphate (cAMP) via pertussis-toxin sensitive inhibitory Gα i proteins (Dinet et al 2007; Lai et al 2008). Activation of the MT 1 receptor promotes inhibition of forskolin-stimulated cAMP formation, suppression of Protein kinase A (PKA) activity, and phosphorylation of the cAMP-responsive element-binding protein (CREB) (Kiefer et al 2002; Dinet et al 2007).…”
Section: Melatonin Receptors In Breast Cancermentioning
confidence: 99%
“…The relevance of melatonin (1) to another autonomous circadian oscillator located in the CNS, but outside the SCN has been reported for the murine retina [125,126]. In the melatonin-deficient mouse strain C57BL, no significant rhythmicity of the clock proteins PER1 and CRY2 and of pCREB was demonstrable, whereas prominent oscillations were seen in the melatonin-proficient strain C3H.…”
Section: Effects Of Melatonin In the Central Nervous Systemmentioning
confidence: 94%